2017
DOI: 10.1039/c7ta05720b
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing perovskite solar cell performance and stability by doping barium in methylammonium lead halide

Abstract: The power conversion efficiency of perovskite solar cells can be enhanced by using Ba2+-doped perovskite films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 42 publications
1
78
1
Order By: Relevance
“…The existence of the PbI 2 peak at 12.718 indicates the incomplete phase transformation of the pristine film ( Figure 1a). [35] Additionally,i ti si nteresting that new diffraction peaks for three MD perovskites appear at about9 .458,c orresponding to the (0 20)c rystal planes( as indicated in Figure 1a and b). Figure 1c and dd isplay the magnified XRD patterns at 13.58-15.58 and 28.08-29.58 of the perovskite films.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…The existence of the PbI 2 peak at 12.718 indicates the incomplete phase transformation of the pristine film ( Figure 1a). [35] Additionally,i ti si nteresting that new diffraction peaks for three MD perovskites appear at about9 .458,c orresponding to the (0 20)c rystal planes( as indicated in Figure 1a and b). Figure 1c and dd isplay the magnified XRD patterns at 13.58-15.58 and 28.08-29.58 of the perovskite films.…”
Section: Resultsmentioning
confidence: 91%
“…It is observed that the positions of the (110)a nd (2 20)c rystal planes for the three MD perovskite films all show slight blueshifts to bigger angles owing to the different ionic radii of Zn 2 + ,M n 2 + ,a nd Ni 2 + (74, 80, and 72 pm), which are smaller than that of Pb 2 + (119 pm). [35] Additionally,i ti si nteresting that new diffraction peaks for three MD perovskites appear at about9 .458,c orresponding to the (0 20)c rystal planes( as indicated in Figure 1a and b). It illustratest hat 2D perovskite structures are formed in the MD perovskites.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Since both injection and extraction barriers are detrimental to the device performance, adequate charge transport materials should be selected for reducing the energy mismatch and minimizing the energy loss at the perovskite interfaces. Previously, many studies focused on the direct comparison between the IPs of perovskites and HTLs so as to evaluate the ELA at their interfaces according to the assumption of flat band situation . Unfortunately, such an IP difference is unlikely the determinable factor for estimating the real ELA, since charge transfer and chemical reaction can lead to the vacuum level shift or band bending.…”
Section: Energetics Of Perovskites and Their Interfacesmentioning
confidence: 99%